The effect of 7 days of creatine supplementation on 24-hour urinary creatine excretion - Burke, D. G.; Smith-Palmer, T.; Holt, L. E.; Head, B.; Chilibeck, P. D. (The Journal of Strength and Conditioning Research, 2001)
Since the discovery that oral ingestion of creatine leads to an increase in intramuscular creatine, its supplementation has become widespread. However, the dosage necessary to maximize retention and create significant increases in intramuscular creatine is poorly understood. In this study, 24-hour urinary creatine and creatinine levels of 20 university men's football players and 20 university men's hockey players involved in a resistance-exercise program and supplementing with creatine were collected and analyzed. In a double-blind, randomized design, 10 football players and 10 hockey players were randomly assigned to either the supplement or placebo group. Subjects provided a 24-hour urine sample twice during the study: once prior to supplementation (baseline) and the second 7 days after daily supplementation and resistance exercise. Creatine dosage was 0.1 g·kg1 lean body mass. The quantity of creatine ingested was compared with the amount excreted in the urine of those subjects supplementing with creatine and with placebo. Creatinine levels were compared between the first and second urine collection and between groups. Creatine and creatinine concentrations were determined using high-performance liquid chromatography. In 24-hours, 46% of the ingested creatine was excreted. There was no change in creatine levels for placebo subjects. Creatinine levels remained the same within groups at the first and second collection times (p ;lt 0.05). Our findings indicate that when supplementing with dosages of 0.1 g·kg1 lean body mass or between 6 and 8 g at a time, approximately half of the ingested creatine gets excreted. Because there was no change in urinary creatinine, it can be assumed that enhanced degradation of creatine did not occur.